(untitled) (Al-Qamar, 2019)
Ḥāfiẓ Jamāl Allah Multānī (d.1226/1811) was a leading Chishtī Sufi Shaykh who established his Khānqāh and Madrasa in Multan and taught his disciples Ḥadīth and other Islamic sciences along with their training in Chishtiyah Sufi order. The present paper aims to present Multānī’s biographical account and his contribution in the fields of Ḥadīth and Sufism as illustrated by his well-known disciple Mawlānā ʻAbd al-‘Azīz Parhārvī (d.1239/1824) in his “Anwār-Jamāliyah”. It finds that both of Multānī’s mentors Khawāja Noor Muhammad Mahārvī (d. 1205/1790) and his Shaykh Khawāja Fakhr al-Dīn Dehlawī (d.1197/1784) were experts in Ḥadīth sciences and both had transferred their relevant knowledge to Multānī. Subsequently, Multānī guided his students both in Ḥadīth and Sufism. His Khānqāh and Madrasa became centre of excellence for Islamic learning, and a large number of scholars and common people received their religious education and spiritual inspiration from this Khānqāh.